Synthesis, Identification, Theoretical and Experimental Studies for Carbon Steel Corrosion Inhibition in Sea Water by Some New Schiff base Derivatives linkage to 5-Nitro Isatin Moiety - Athraa H. Ahmed (Journal of Global Pharma Technology, 2018)
This research includes synthesis of new 5-Nitro isatin derivatives started from 5-Nitro-3-(Ethyl imino acetate)-2-oxo indol, namely 5-Nitro-3-(imino acetohydrazide)-2-oxo indole (1); 5-Nitro-3-[(iminoacetyl) phenylsemi carbazide]-2-oxo indole (2); 5-Nitro-3-[(imino acetyl) phenylthiosemicarbazide]-2-oxo indole (3); and 5-Nitro-3-[(imino aceto) N,N-di methyl urea]-2-oxo indole (4). The derivatives were characterized by using FTIR, 1H-NMR, 13C-NMR and C.H.N.S analysis with the measurement of some physical properties. Quantum mechanical method of the Density Functional Theory (DFT) of B3LYP with a level of 6-311++G (2d, 2p) were used for calculating the geometrical structure, physical properties and inhibition efficiency parameters, all were studied at the equilibrium geometry in four media (vacuum, DMSO, ETOH and H2O). The theoretical results showed that compound (2) is the best corrosion inhibitor among the others. Finally, the corrosion protectiveness, kinetics, and thermodynamics of the prepared compound (2) effect on C-steel in 3.5% NaCl solutions had been studied using the potentiodynamic polarization, SEM (Scanning Electron Microscopy) and AFM (Atomic Force Microscopy) measurements.Keywords: 5- nitro isatin, Schiff bases, Corrosion inhibitors, Quantum chemical calculations, electrochemical measurements.